Molecular Pharmacology of P2X Receptors: Exploring Druggable Domains Revealed by Structural Biology - Oken, Adam C.; Krishnamurthy, Ipsita; Savage, Jonathan C.; Lisi, Nicolas E.; Godsey, Michael H.; Mansoor, Steven E. (Frontiers in Pharmacology, 2022)
Extracellular ATP is a critical signaling molecule that is found in a wide range of concentrations across cellular environments. The family of nonselective cation channels that sense extracellular ATP, termed P2X receptors (P2XRs), is composed of seven subtypes (P2X1-P2X7) that assemble as functional homotrimeric and heterotrimeric ion channels. Each P2XR is activated by a distinct concentration of extracellular ATP, spanning from high nanomolar to low millimolar. P2XRs are implicated in a variety of physiological and pathophysiological processes in the cardiovascular, immune, and central nervous systems, corresponding to the spatiotemporal expression, regulation, and activation of each subtype. The therapeutic potential of P2XRs is an emerging area of research in which structural biology has seemingly exceeded medicinal chemistry, as there are several published P2XR structures but currently no FDA-approved drugs targeting these ion channels. Cryogenic electron microscopy is ideally suited to facilitate structure-based drug design for P2XRs by revealing and characterizing novel ligand-binding sites. This review covers structural elements in P2XRs including the extracellular orthosteric ATP-binding site, extracellular allosteric modulator sites, channel pore, and cytoplasmic substructures, with an emphasis on potential therapeutic ligand development.